2013
DOI: 10.1021/cg400308a
|View full text |Cite
|
Sign up to set email alerts
|

A Simple Method To Control Morphology of Hydroxyapatite Nano- and Microcrystals by Altering Phase Transition Route

Abstract: Hydroxyapatite (HAp) particles with various morphologies such as sphere, rod, whisker, and platelet have attracted a great deal of scientific and technological interest for their broad utilization as reinforcing agents in bone cement, bone fillers, drug carriers, and adsorbents for chromatography. In this Article, a simple method to control the morphology of HAp particles by adjusting the initial pH of precursors and the amount of gelatin and urea additions is introduced. Initially formed calcium phosphate pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(24 citation statements)
references
References 29 publications
0
24
0
Order By: Relevance
“…The and 12 is ‫ܱܲܽܥ‬ ସ ି . Under this conditions it has been postulated a shift on the surface charge of the mineral leading to the precipitation of amorphous calcium phosphate [24],…”
Section: Effect Of Ph In Hap Precipitationmentioning
confidence: 99%
See 1 more Smart Citation
“…The and 12 is ‫ܱܲܽܥ‬ ସ ି . Under this conditions it has been postulated a shift on the surface charge of the mineral leading to the precipitation of amorphous calcium phosphate [24],…”
Section: Effect Of Ph In Hap Precipitationmentioning
confidence: 99%
“…Han et al [24] identified at pH 10, the precipitation of an amorphous calcium phosphate (ACP) phase at the initial reaction time and then it crystallized into Hap after 2h of reaction.…”
Section: Effect Of Ph In Hap Precipitationmentioning
confidence: 99%
“…Han et al have reported a method for controlling the HAp nanoparticle morphology under hydrothermal treatment in the presence of urea and gelatin. They synthesized various HAp morphologies by altering the phase transition route by varying the initial pH and hydrothermal treatment time [23]. Kawachi [27,28].…”
Section: Introductionmentioning
confidence: 99%
“…11 Phase purity and crystal shape can also be controlled by adding organic can be obtained. 12 The crystallinity of the material is another important aspect, since it governs dissolution properties and subsequently effects the biodegradation/bioresorption. 14 Temperature and pH are two major parameters that determine the crystallinity of ceramic material produced by precipitation method.…”
Section: Introductionmentioning
confidence: 99%